IMPACT OF CONFLICT MANAGEMENT ON EMPLOYEES' PERFORMANCE IN A PUBLIC SECTOR ORGANISATION IN NIGERIA - Olu, OJO; Dupe Adesubomi, ABOLADE (Strategii Manageriale)
This study investigated the impact of conflict management on employees’ performance in a public sector organisation, a case of Power Holding Company of Nigeria (PHCN). This study adopted the survey research design. A total of 100 respondents were selected for the study using stratified sampling technique. Questionnaire was used to collect primary data. Data collected were analysed using descriptive statistics. Hypotheses were tested through regression analysis and correlation coefficient. The findings revealed that effective conflict management enhance employee’s performance in an organisation and that organisation’s conflict management system influences employee performance in the organisation. It was recommended that organisation should embark on training and retraining of its employees in area of conflict management so as to create a conductive working environment for the employees and that there should be efficient and effective communication between and among all categories of the employees the organisation. This will reduce conflicting situations in the organisation.